Productive Zakat As An Alternative Islamic Social Financial Instrument In Community Economic Empowerment Reflection Of The Covid-19 Era - Dina Arfianti Siregar; Saparuddin Siregar; Marliyah Marliyah (Publikasi Indonesia, 2023)
The Muslim population that has great potential in giving zakat is Indonesia. One of the functions of zakat is as a social fund that can be used to overcome social problems such as poverty that occurs in society. Of course, an appropriate formulation is needed to utilize zakat assets to overcome these social problems. Among the efforts is to build a paradigm that the use of zakat must be productive, educational, and economical so that in the end, zakat recipients (mustahiq) will leave the mustahiq zone and will automatically enter the mandatory zakat zone (muzak). Productive zakat is giving zakat that can make recipients produce something continuously through the zakat assets they have received. This program can not only help underprivileged people. However, it can also enable people who have been economically deprived and have always been zakat recipients to change their position to become muzakki. This research describes productive zakat and its empowerment in Indonesia. Apart from that, we also found that productive zakat is very powerful in playing its role as one of the sharia financial instruments in Indonesia in empowering and alleviating poverty through the philanthropic institutions that support it.